CLATHRATE HYDRATES - Buffett B.A. (My University, 2000)
Substantial volumes of methane gas are trapped below the seafloor and in permafrost by an ice-like solid called clathrate hydrate. Global estimates of the methane in clathrate hydrate may exceed 1016 kg, which represents one of the largest sources of hydrocarbon on Earth. Speculations about large releases of methane from clathrate hydrate have raised serious but unresolved questions about its possible role in climate change. Progress in our understanding of clathrate hydrate has been made through integrated geophysical and geochemical surveys of known clathrate occurrences. Details from these surveys have motivated new investigations of the physical, chemical, and biological processes that contribute to growth and breakdown of clathrate hydrate in natural settings. In this article, I give an overview of recent advances and future challenges.